Tingkat Kedisiplinan Siswa Kelas IX SMP Negeri 6 Semarang - Aris, Abdul; Ismanto, Heri Saptadi; Kusumawati, Mia Indah (Jurnal Penelitian Multidisiplin Ilmu, 2024)
Discipline is an important aspect for students to achieve optimal learning outcomes. High discipline is one of the factors that can help students achieve achievement in learning and good character building. Vice versa, students who have low self-discipline will achieve less than optimal learning outcomes and poor character. From this, the researcher will examine the level of discipline at SMP N 6 Semarang. The sample of this research is ninth grade students of SMP N 6 Semarang which amounted to 139 respondents. For data collection methods using how to distribute questionnaires through google form social media applications WhatsApp Group. Research results in the very low category with a percentage of 0% low category of 15.11% medium category of 67.63% and in the very high category of 17.27%. And the overall results in this category can be concluded that class IX students of SMP N 6 Semarang have moderate category discipline. Translated with DeepL.com (free version)